The gunslinger - King, Stephen, 1947- (King, Stephen, 1947- Dark tower, 2016)
In The Gunslinger, King introduces Roland Deschain of Gilead, the Last Gunslinger. He is a haunting, solitary figure at first, on a mysterious quest through a desolate world that eerily mirrors our own. Pursuing the man in black, an evil being who can bring the dead back to life, Roland is a good man who seems to leave nothing but death in his wake.